2016
DOI: 10.3340/jkns.2016.59.5.425
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Effect of Rod Contouring on Rod-Screw System Strength in Spine Fixation

Abstract: ObjectiveRod-screw fixation systems are widely used for spinal instrumentation. Although many biomechanical studies on rod-screw systems have been carried out, but the effects of rod contouring on the construct strength is still not very well defined in the literature. This work examines the mechanical impact of straight, 20° kyphotic, and 20° lordotic rod contouring on rod-screw fixation systems, by forming a corpectomy model.MethodsThe corpectomy groups were prepared using ultra-high molecular weight polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Moreover, it is concluded from biomechanical studies that work energy required for failure of kyphotic rod is lesser than that of a lordotic rod in a corpectomy model. [ 20 ] We feel that the unaddressed PJK because of delayed follow-up in the first and third case could have led to more stress at the VCR zone causing rod breakage at the site of VCR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is concluded from biomechanical studies that work energy required for failure of kyphotic rod is lesser than that of a lordotic rod in a corpectomy model. [ 20 ] We feel that the unaddressed PJK because of delayed follow-up in the first and third case could have led to more stress at the VCR zone causing rod breakage at the site of VCR.…”
Section: Discussionmentioning
confidence: 99%
“…In this present experimental study, strain in rod at L4-L5 segment found as 250 microstrain for 8 Nm flexion and 340 microstrain for FE analysis. Acar et al (2016) performed mechanical testing on a corpectomy model under a compressive force of 100 N with 8.4 Nm moment in flexion-extension for different rod (titanium) curvatures (straight, kyphotic and lordotic) and found the mean values of strain for straight, kyphotic and lordotic rods as 1086 microstrain, 1244 microstrain and 1124 microstrain respectively under extension conditions [18].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In an experimental study performed with a corpectomy model to investigate the effects of straight, lordotic, and kyphotic rod contouring on the rod-screw fixation system, the lordotic system was found to be the most rigid one and the failure risk of rod-screw fixation was much higher than that of the kyphotic system. 6 Another experimental study demonstrated that rod contouring using a French bender affected the mechanical properties of the rods with the application of 0°, 10°, 20°, and 40° tangential rod bending angles. 7 That study concluded that rod contouring caused a reduction in yield strength and the stiffness of rods according to the degree of bending.…”
Section: Introductionmentioning
confidence: 99%